Comparison on physical properties of juvenile and matured Gigantochloa albociliata - Rahman, Mohd Emran (2019)
Bamboo is a multipurpose plant that have a broad and plentiful of applications beyond imagination. For Gigantochloa albociliata, it is commonly used as edible shoots in some countries including Malaysia. The study aim was to identify the physical properties of Gigantochloa albociliata according to the parts and ages. From the result, it was found that the physical properties of Gigantochloa albociliata on each parts and ages have a significant different for each characteristics except for moisture content and bamboo height which both of it do not have a significant different. The best part of Gigantochloa albociliata was bottom part. Meanwhile, the best age of Gigantochloa albociliata was matured.